A Type-2 Fuzzy Controller for Floating Tension-Leg Platforms in Wind Turbines - Firouzi, Behnam; Alattas, Khalid A.; Bakouri, Mohsen; Alanazi, Abdullah K.; Mohammadzadeh, Ardashir; Mobayen, Saleh; Fekih, Afef (Energies (Basel), 2022)
This paper proposes a type-2 fuzzy controller for floating tension-leg platforms in wind turbines. Its main objective is to stabilize and control offshore floating wind turbines exposed to oscillating motions. The proposed approach assumes that the dynamics of all units are completely unknown. The latter are approximated using the proposed Sugeno-based type-2 fuzzy approach. A nonlinear Kalman-based algorithm is developed for parameter optimization, and linear matrix inequalities are derived to analyze the system’s stability. For the fuzzy system, both rules and membership functions are optimized. Additionally, in the designed approach, the estimation error of the type-2 fuzzy approach is also considered in the stability analysis. The effectiveness and performance of the proposed approach is assessed using a simulation study of a tension leg platform subject to various disturbance modes.